2014
DOI: 10.1007/s11999-013-3134-0
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Results Suggest Tranexamic Acid is Safe and Effective in Arthroplasty Patients with Severe Comorbidities

Abstract: Background Tranexamic acid (TXA) reduces blood loss and transfusion after total joint arthroplasty (TJA) but concerns remain that patients with severe medical comorbidities might be at increased risk for thromboembolic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
78
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 27 publications
(42 reference statements)
3
78
0
2
Order By: Relevance
“…Next, the population of patients was expanded to review patients that had significant comorbidities, including patients that were determined to be American Society of Anesthesiologists score III or IV. Once again, we saw no significant difference in thromboembolic events, however there was a significant reduction in the transfusion rates for those that received TXA [15] . Finally, we have confirmed that TXA use is associated with decreased costs.…”
mentioning
confidence: 69%
“…Next, the population of patients was expanded to review patients that had significant comorbidities, including patients that were determined to be American Society of Anesthesiologists score III or IV. Once again, we saw no significant difference in thromboembolic events, however there was a significant reduction in the transfusion rates for those that received TXA [15] . Finally, we have confirmed that TXA use is associated with decreased costs.…”
mentioning
confidence: 69%
“…Caution was exercised with regard to whether IV-TXA would further disturb coagulation in these patients who were at risk for thromboembolic events. In a trial of high-risk patients who were ASA III-IV conducted by Whiting et al (37), TXA was not associated with an increase in symptomatic thromboembolic events (6.7% vs. 4.3%; p = 0.270) and was associated with a decrease in transfusion rates (17% vs. 48%; p = 0.001). Similarly, the current findings revealed few differences in the TEG parameters of all four groups, suggesting that both TXA and FS slightly affect coagulation in patients with severe comorbidities.…”
Section: Discussionmentioning
confidence: 93%
“…Theoretically, the use of TXA carries a risk of thromboembolism, although it has not been proved clinically. 5,[28][29][30][31] There have been rather several reports of a lower incidence of thromboembolism in groups with TXA. 32,33 Several reasons for the absence of increased thromboembolism in the TXA group, including a decreased need for allogenic transfusion, have been suggested.…”
Section: Discussionmentioning
confidence: 99%